Educating the principals of Linguistic Universal in Concept «Nature» - S. Kh., Shikhalieva (2020)
The article is concerned with educating  the concepts  “proper name * toponym + anthroponym” linguocultural category and summarizing the analysis with regard to cognitive perception of Nakh-Dagestanian languages. If we consider the interpretation of the terms “proper name * toponym + anthroponym” from viewpoint of cognitive perception, then the world picture as a linguocultural category actualizes the concept “nature ↔ toponym + color ↔ anthroponym + color”. This procedure for analyzing the terms in the conceptualization of the Nakh-Dagestanian languages makes it possible to adjust the interpretation of the Russian language “Concept “nature” ↔ color + toponym ↕ color + anthroponym”. An analysis of the material shows that the interpretation of the terms with the designation of the concept “nature” differs in hierarchical types of asymmetry of the Nakh-Dagestanian languages of ordered types “class ↔ class member”, and the degree of influence of the scientific world picture on the meaning of the everyday picture of the region is usually structured by the analysis of translation into the Russian language.